Female genital tuberculosis: a clinicopathological study - Desai, Rathnamala M.; Kumar, Sunil; Brindini, Usha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The aim of this study was to describe the various clinical presentations of female genital tuberculosis and study the different methods of diagnosis and treatment. Methods: A study of all cases of female genital tuberculosis diagnosed in the last five years was done. Results: Female genital tuberculosis was diagnosed in 25 cases over a period of five years. Majority of the women (60%) were in the younger age group. Most of the women (60%) presented with infertility. Twelve (48%) women had primary infertility and 3 (12%) had secondary infertility. Nine (36%) women had secondary amenorrhea. Five (20%) women complained of abdominal pain. Thirteen (52%) women who underwent diagnostic hysterolaparoscopy as a part of evaluation for infertility were diagnosed to have genital tuberculosis. Genital tuberculosis was diagnosed by endometrial biopsy or biopsy from the tubercles if present. Genital tuberculosis was diagnosed by laparotomy in 4 cases. Four women underwent salpingectomy. Two women underwent excision of Tubo-ovarian mass. One woman had intestinal resection. All cases were treated with anti-tubercular drugs. Conclusions: Genital tuberculosis frequently causes infertility and secondary amenorrhea. In a country like India where tuberculosis is endemic a clinician should have a high degree of suspicion when evaluating cases of infertility and secondary amenorrhea.